Editorial - Medina Castro, Darío Emiliano (2021)
The National Autonomous University of Tayacaja Daniel Hernández Morillo, presents Vol. 4 No. 2 (2021) of the Revista de Investigación Científica TAYACAJA, which is an indexed scientific publication, edited by the vice-presidency of research and is aimed at the publication of scientific articles originals in the areas of Engineering, Biodiversity and Environment.